Creative approaches in making objects of identification for Ukrainian companies - Kolisnyk, Oleksandra; Krotova, Tetiana; Hovhannisyan, Solomiya; Pshinka, Natalia; Osadcha, Alla (Creativity Studies, 2025)
The article is devoted to the study of creative approaches of design and advertising specialists in creating logos and trademarks of the companies of Ukraine, other countries of Europe, North America, and the East Asia, that have been successfully operating in the market for at least ten years. Examples of font and image solutions aimed at solving a set of problems have been considered: brand identification among others, product or service advertising, forming the visual image of the company in the consumer’s mind. The authors believe that the environment of visual signs and messages is a system of various human impressions, indications of needs, and ways to meet them, which requires a “creator”, endowed with the gift of intuitive insight into the pictorial essence of things, needs and phenomena and able to convince consumer in the understanding of their image. Logos of various global companies (manufacturers of food, industrial, pharmaceutical products, service companies and others) are classified into eight groups by structural and compositional characteristics. Based on the analysis of market positioning of companies and their communication strategies, the authors conclude that the basis for identifying the creative component in the development of brand identity is the relationship between production processes and positioning of goods (services) and the sensory-emotional sphere of the consumer.